Motivasi Petani dalam Membudidayakan Tanaman Pepaya Calina (Carica papaya L) (Kasus Kelompok Tani Pepaya Calina di Desa Sulangai, Kecamatan Petang, Kabupaten Badung) - DEWA PUTU GEDE SATRIA WIWEKA; I DEWA PUTU OKA SUARDI; A.A.A WULANDIRA SAWITRI DJELANTIK (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
The Farmer’s Motivation In Cultivating The Papaya Calina Plant(Carica papaya L) (The Farmer’s Group of Calina Papaya at Sulangai Village, onPetang District, in Badung Regency). Sulangai village is the village where most of the villagers work as a farmer. One of thefarmer’s work done by the farmer in that village is papaya calina. Based on thedescription above, it’s interesting to analyze about the motivation faced by the farmer incultivating the papaya calina plant at Sulangai village, on Petang district, in Badungregency. The purpose of this research is to know the farmer’s motivation in cultivatingthe papaya calina plant at Sulangai village, on Petang district, in Badung regency. Theresearch held at sulangai village, on Petang district, in Badung regency particularly infarmer’s group of papaya calina. The location of the research is based on the purposivemethod which is determination of the research location deliberately. The population inthis research is 20 farmers.Based on the research data, the intrinsic motivation of the farmer cultivating the papayacalina plant at Sulangai village, on Petang district, in Badung regency is categories highpercentage about 70,81%. The intrinsic motivation of the farmer in cultivating thepapaya calina plant generally categories in high percentage about 79,09%.Based on theresearch the farmer’s group as the one who does this job is brave to try this technologyin cultivating the papaya calina plant which is given by the instructor. By trying thetechnology, the farmer’s group will get more new experiences to do in cultivatingpapaya calina in the future.